Pengaruh Kebersihan Terhadap Konsentri Belajar Santri Putra Kobong L Di Pondok Pesantren Darul Falah Cihampelas - Muhammad Farid Ramdani; Bayu Setiawan; Fauzan Zaeni Zakcy (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
This study aims to investigate the impact of cleanliness on the learning concentration of male santri Kobong L at the Darul Falah Cihampelas Islamic boarding school. Our research uses quantitative methods in the form of a questionnaire distributed to 27 male students of Kobong L. The benefit of this research is to gain an understanding of the influence of cleanliness on learning concentration. The results show that Kobong L is still not clean because rubbish is still found in it, therefore, it is important to collaborate and maintain cleanliness so that you are comfortable and focused when studying.